Reorientable fluorinated aryl rings in triangular channel Fe-MOFs: an investigation on CO2–matrix interactions. Issue 22 (1st June 2020) - Perego, J.; Bezuidenhout, C. X.; Pedrini, A.; Bracco, S.; Negroni, M.; Comotti, A.; Sozzani, P.
Abstract : Flexible aryl rings in fluorinated Fe-MOFs point C–F dipoles towards the corner of triangular channels capturing efficiently CO2 molecules. Abstract : The realization of tunable and functionalized MOFs is a winning strategy for CO2 capture. Here we report on a series of robust Fe-MOFs with triangular channels constructed by rod-like fluorinated pyrazolate ligands, comprising an increasing number of fluorine atoms on the central p -phenylene core (F = 1, 2, and 4). This yielded a series of isoreticular frameworks, engineered with orientational flexibility of the fluorinated aryl rings pivoted on ethynyl groups with an sp 2 –sp soft rotary barrier, providing a stable axel, which supported reorientable C–F dipoles. A combined approach, including powder X-ray diffraction, multinuclear solid-state NMR (2D 1 H– 13 C, 19 F, hyperpolarized 129 Xe NMR and distance measurements by paramagnetic shift), gas-adsorption and microcalorimetry, enabled the exhaustive description of the fluorinated ring arrangement and the organization of functionalized sites for accommodating CO2 . In the tetrafluoro-aryl-derivative MOF, protrusion of perfluorinated rings towards the channel space plays a major role in CO2 capture. Partially fluorinated aryl rings of mono- and di-fluoro MOFs turn to retract into the channel-walls to form continuous ribbons of inter-strut supramolecular interactions, contributing to the robustness of the overall architecture. Detailed computational models obtained using GCMC and DFT of CO2 diffusion and interactions in MOFs showed how the gas molecules approach the channel walls. The highly occupied sites are aligned at the corners of the triangular channels, wherein fluorine atoms participate in host–CO2 interactions. A CO2 –matrix adsorption enthalpy of 33 kJ mol −1, suitable for capture/delivery cycles, was accurately measured in situ by simultaneous acquisition of microcalorimetric and volumetric-isotherm data. Thus, the designed advantages of rotationally flexible fluorinated moieties were successfully explored.